Customers’ Intention to Purchase Halal Products in Malaysia: A Case of Non-Muslims - Yeow, Chin Chai (2019)
In today’s modern society, people are more concern about the food they purchase and consume. The issues of food poisoning and unethical food preparation and sources had caused the concern around the world, especially in a less developed country. Therefore, people tend to be more cautious about the source of the ingredients, the preparation process and finished products in the market. As the advancement of the information technology, customers were more educated and information is easily available by just-a-click on the search engine. Hence, there will be more consumers looking for products with quality and safe to consume. In a Muslim country, halal products were a norm in the society whereby the halal products were not only being consumed by Muslims in their daily life, the acceptance of non-Muslims towards the halal food products is growing as well because of the strict process and laws to follow. Besides, the halal food products are also being monitored, certified and enforced by the government. Halal product with certification will automatically gain the confident of the customers without any doubts. Therefore, this study tends to examine the intention of non-Muslim customers in purchasing halal food products in Klang Valley. Six independent variables are being adapted and adopted in this research to identify the intention of non-Muslim customers to consume halal food products which are product quality, product price, product availability, product ingredients, product awareness and product safety. A total of 321 respondents from Klang Valley area were participated and responded in this survey. Based on the findings and analysis, this study revealed that there are three independent variables that have positive significant relationship in affecting the intention of non-Muslim customers to purchase halal food products which are product quality, product price and product availability. Hopefully, these findings can be used by the government and private sector to further develop the halal industry locally and internationally. Lastly, based on the findings, the researcher also suggested a few proposals for further study and improvement.